Hepatitis B vaccination policies and coverage for nurse working at public and private hospitals in Tshwane, South Africa - Mureithi, John Gachagua (University of Limpopo (Medunsa Campus), 2009)
BACKGROUND AND AIM: Hepatitis B virus (HBV) is the major cause of hepatitis in South Africa (SA), with an estimated 4 million carriers. It is transmitted by infected blood and other body fluids, placing health care workers (HCWs) at high risk of infection. The SA Department of Health strongly recommends that all HCWs be vaccinated against HBV, but studies have shown that uptake of the vaccine is sub-optimal. This study aimed to estimate HB vaccination coverage levels among nurses, and describe the demographics and characteristics of the HB vaccination policies associated with different levels of coverage, at private and public hospitals in Tshwane. METHODS: This was a questionnaire-based cross-sectional study on 300 randomly selected nurses and 12 chief infection control officers (CICOs) from 13 hospitals (6 public and 7 private) in Tshwane performing high risk procedures. CICOs were asked questions about HB vaccination policies and coverage, while nurses were asked about demographics, HB vaccination status, and the HB vaccination policies of their institutions. RESULTS: The response rate was 84.3% (253/300) for nurses, and 75% (9/12) for CICOs. Of the nurses, 68.0% (172/253) were vaccinated, and logistic regression analysis found that those statistically significantly most likely to be vaccinated were: 30 years and younger (odds ratio [OR]=2.9; 95% CI: 1.11–7.59); employed in private hospitals (OR=3.0; 95% CI: 1.24–7.32); and graduated after 1990 (OR=2.6; 95% CI: 1.10–6.19). Also, logistic regression analysis found two statistically significant policy-related predictor for vaccination uptake, which was the presence of HB vaccination program (OR=4.6; 95% CI: 2.11-10.06); and compulsory HB vaccination (OR=2.8; 95% CI: 1.37-5.70. CONCLUSION: There is a need for a national policy on HB vaccination of HCWs which should include compulsory vaccination, to increase the vaccination coverage level amongst nurses.
Thesis (MPH)--University of Limpopo, 2009.
Keywords: Hepatitis B; Vaccination policies